Laboratory Evaluation of Natural Decay Resistance and Efficacy of CCA-Treated Rubberwood (Hevea brasiliensis Muel!. Arg.) - Jusoh, Ismail; Kamdem, D. Pascal (Walter de Gruyter, 2001)
Information on the natural decay resistance and efficacy of CCA-treated rubberwood is important for the development rubberwood industry. The purpose of this study was to determine the natural decay resistance of rubberwood and the efficacy of CCA-pressure treatment in order to explore a new opportunity for this abundant raw material. Natural decay resistance and efficacy of CCA was estimated using soil-block test according to AWPA ElO-91. Cubes were exposed to six wood-decay fungi: two each from white, brown, and soft rot. The moisture content of test cubes exposed to /rpex lacteus and Trametes versicolor increased with weight loss increase, while that exposed to Gloeophyllum trabeum and Postia placenta decreased. After a 12-week incubation period the average weight loss by white rot and brown rot fungi was about 1.5 times higher than that of soft rot fungi. CCA retention of 4.1 kg/m3 reduced weight loss to between 8 % and 10 %, retention of 14.5 kg/m3 protected weight loss by all test fungi from exceeding2%.